The association between maternal smoking during pregnancy and multimorbidity of non-communicable chronic diseases trajectory in offspring - Hang Wang; Xinyi Sun; Zheng Wang; Hui Liu; Jiaxin Huang; Yiwei Tang; Shanshan Wang; Conghui Qiao; Mengqi Su; Qianqian Lei; Wei Wei; Changhao Sun; et al. (BMC Public Health)
Abstract Objectives Although a few studies have found that maternal smoke during pregnancy (MSDP) is linked to a range of non-communicable chronic diseases (NCDs) in offspring, its association with the onset, progression, and prognosis of multimorbidity of NCDs (MNCDs) has never been studied. Study design Population-based prospective cohort study. Method A total of 318,122 adults aged 18–87 years who were free of heart disease, stroke, and diabetes at baseline were selected. MNCDs was defined as the coexistence of two or three NCDs, including CVDs (coronary heart disease and stroke), cancer (digest, breast, lung, and urination), diabetes (type 1 and type 2), and CLRD (COPD and asthma). Then we used multi-state model to analyse the impacts of MSDP on the progression of MNCDs in the offspring. Associations between MSDP and transition trajectory were analyzed with results expressed as hazard ratio (HR) and 95% confidence interval (95% CI). Results During the 70.2 years of follow-up, a total of 112,894 participants developed first NCDs (FNCDs), among whom 28,195 developed MNCDs and 21,452 subsequently died. After adjustment for potential confounders, the MSDP was associated with the transition trajectory from baseline to FNCD (HR = 1.10, 95%CI:1.09–1.11) and from FNCDs to MNCDs (HR = 1.08,95%CI:1.06–1.10). Meanwhile, the MSDP was associated with the transition trajectory from MNCDs to death (HR = 1.07,95%CI:1.03–1.11). Further, these association became more pronounced among the offspring who smoke (HRbaseline→FNCDs=1.13, 95%CI:1.12–1.15; HRFNCD→MNCD=1.13, 95%CI:1.12–1.15; HRMNCDs→death=1.11, 95%CI:1.16–1.16); whereas among the offspring who do not smoke, only the transition trajectory from baseline to FNCDs was observed (HR = 1.07, 95%CI:1.05–1.09). Conclusion This study suggested that the MSDP is associated with almost all transition phases of MNCDs development and increases the mortality risk of MNCDs in offspring who smoke, and these transition trajectories can be largely reduced by smoking cessation among offspring.